SITE INDICATOR SPECIES FOR PREDICTING THE PRODUCTIVITY OF TEAK PLANTATIONS IN PHRAE PROVINCE, THAILAND - Narinthorn Jumwong; Chongrak Wachrinrat; Sarawood Sungkaew; Atchara Teerawatananon (SEAMEO BIOTROP, 2020)
Site quality assessment is critically important in any tree planting activity as it may serve a range of management functions such as optimizing productivity estimates of forest plantations. This study aimed to evaluate the site quality, using plant indicator species, for three teak plantations located in Northern Thailand belonging to the Forest Industry Organization (FIO). Twenty-four sample plots were chosen to cover all the growth classes within the age range of 6–39 years. The site index of teak was established by using the anamorphic technique which is based on dominant height and age at a base age of 30 years, divided into 3 site index classes as 24, 21, and 18, as good, moderate, and poor site quality, respectively. Associated species, the native species that are tree and shrub habitats, were surveyed in the 24 plots and indicator species were classified using the Indicator Species Analysis (ISA) and Two Way Indicator Species Analysis (TWINSPAN). The relationship between indicator species and environmental factors was analyzed by the Generalized Linear Model (GLM). The associated species were classified into 76 species with 21 families. The results of ISA indicated the significant indicator species under the good site class were Streblus ilicifolius, Lagerstroemia floribunda, Dalbergia cana and Lagerstroemia calyculata; while Schleichera oleosa and Dalbergia nigrescens were presented under poor site class, respectively. The results from TWINSPAN supported Streblus ilicifolius, Lagerstroemia floribunda and Schleichera oleosa were obvious indicators. Each indicator species distribution was influenced by various relationships with environmental factors, in which soil pH and N were the main factors to distribute all indicator species to 3 relationships. First, the indicator species positively associated with soil pH and negatively associated with N were Streblus ilicifolius and Dalbergia nigrescens. Second, the indicator species positively associated with soil pH and N were Lagerstroemia floribunda and Schleichera oleosa. Third, the indicator species negatively associated with soil pH and positively associated with N were Dalbergia cana and Lagerstroemia calyculata. The GLM analysis revealed P, Ca and elevation influenced indicator species distribution. As of writing, this is the first study on species indicators for suitable sites of teak in Thailand. Meanwhile, in the absence of confirmatory studies, these indicators can be used as a guide for farmers interested in planting teak. In bare lands, the farmer can apply these indicator species to determine the site quality based on the species' past appearance.